Paiements pour services environnementaux et vulnérabilité des populations locales dans les pays du Sud – Études de cas costaricien et congolais - Géraldine Froger; Pierre Alexandre Maizière; Thomas Legrand (Développement Durable et Territoires)
By means of an institutionalist ecological economics perspective combined with the sustainable livelihoods approach, this article analyses the opportunities and risks of payments for environmental services (PES) schemes to reduce vulnerability to poverty of local populations. Our article is comparing two fields of study: Costa Rica (CR) and the Democratic Republic of Congo (DRC). The Costa Rican program generally reduces vulnerability. But its effects are unequally distributed to the detriment of the poor, marginalized in this scheme. In DRC, the PES scheme doesn’t reduce vulnerability of local populations who remain trapped in poverty.